The Meaning Of Randai Training In Karang Taruna Batuang Sarumpun - Khairiyah Widiya Kusuma; Vevi Sunarti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
The background of this research is the phenomenon of Karang Taruna Batuang Sarumpun, Batuang Taba Village, Lubuak Bagaluang District, Padang City as the only Youth Organization that has a Minangkabau cultural arts community in which randai training, in which the program management is well managed. This study aims to determine the meaning of randai training in terms of program management aspects, namely: setting goals, determining participants, determining facilitators, determining learning methods, determining and presenting material, implementation, monitoring and evaluation. This type of research is a qualitative research with a case study method. The data sources in this study consisted of research informants, namely the training manager and the randai participants themselves. The data collection techniques used were observation, interviews, and documentation with data analysis used, namely data reduction, data presentation, and drawing conclusions as well as the validity of the data from research conducted with extended participation, persistence of observation, and triangulation. The results showed that: (1) Karang Taruna Batuang Sarumpun Padang carried out randai training activities with the program management running well; (2) The purpose of this randai training activity has been carefully discussed, namely to preserve Minangkabau cultural arts that are carried out and introduced to the younger generation; (3) Determination of training participants selected from every RT in Batuang Taba Village, the participants are at least grade 2 junior high school and the maximum is not limited; (4) The selection of facilitators is chosen from professional trainers who already have experience in training Minangkabau traditional arts; 5 Determination of learning methods in randai training is determined by the facilitators themselves, namely in the form of lecture methods, and practical methods; (6) The determination and presentation of the material from this randai training is left to the randai facilitator himself; (7) The activities are carried out in the secretariat room of the Youth Organization itself, starting at 20.00 WIB until 21.30 WIB every Thursday and Sunday; and (8) The monitoring and evaluation of the randai training is carried out during the randai training activity process, for the evaluation of the participants is carried out when they will appear for the baralek event and competition